2016
DOI: 10.1002/biot.201600008
|View full text |Cite
|
Sign up to set email alerts
|

A dual enzyme system composed of a polyester hydrolase and a carboxylesterase enhances the biocatalytic degradation of polyethylene terephthalate films

Abstract: TfCut2 from Thermobifida fusca KW3 and the metagenome-derived LC-cutinase are bacterial polyester hydrolases capable of efficiently degrading polyethylene terephthalate (PET) films. Since the enzymatic PET hydrolysis is inhibited by the degradation intermediate mono-(2-hydroxyethyl) terephthalate (MHET), a dual enzyme system consisting of a polyester hydrolase and the immobilized carboxylesterase TfCa from Thermobifida fusca KW3 was employed for the hydrolysis of PET films at 60°C. HPLC analysis of the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
107
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 25 publications
4
107
0
1
Order By: Relevance
“…; Barth et al . ). For instance, the MHET by‐product of PET hydrolysis is inhibitory of enzymes found in Thermobifida fusca KW3, and glyoxylic acid inhibits Flavobacterium sp.…”
Section: Future Research Needsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Barth et al . ). For instance, the MHET by‐product of PET hydrolysis is inhibitory of enzymes found in Thermobifida fusca KW3, and glyoxylic acid inhibits Flavobacterium sp.…”
Section: Future Research Needsmentioning
confidence: 97%
“…during PEG degradation (Gu ; Barth et al . ). Potential inhibitory effects of plastic degradation by‐products on Pseudomonas species remain to be fully understood.…”
Section: Future Research Needsmentioning
confidence: 97%
“…Thus, the stabilization of MHET concentration from 10 to 14 days of reaction may suggest that this is a limiting condition for MHET accumulation; however, systematic enzyme kinetic studies are needed to support the hypothesis of inhibition by MHET, as done by Barth et al [2]. At 14 days of reaction, TPA was the main product of the reactions in the seven substrates (χ TPA = 0.552-0.938), with the only exception being when HiC was used as the only biocatalyst for amorphous PET hydrolysis (χ TPA and χ MHET were 0.494 and 0.495, respectively).…”
Section: Synergy Studies On Different Pet Samplesmentioning
confidence: 99%
“…The simultaneous use of two enzymes for PET film hydrolysis was investigated by Barth et al [2]. Authors used a T. fusca carboxylesterase (TfCa) to complement the good PET depolymerizing activity of either a T. fusca cutinase or a metagenome-derived LC-cutinase, and observed that the higher the amount of TfCa, the higher the proportion of TPA over MHET.…”
Section: Synergy Studies On Different Pet Samplesmentioning
confidence: 99%
See 1 more Smart Citation